Maqashid As-Ayariʻah sebagai Dasar Pengembangan Ekonomi Islam - Nasitotul Janah; Abdul Ghofur (International Journal Ihya' 'Ulum al-Din, 2018)
In contrast to the secular economy of capitalism and socialism, Islamic Economy is the one built on syariʻah bases, norms and divine transcendent values  in the divine revelation, the al-Qurʻan and the ḥadiṡ. In order to understand the essence of syariʻah, it is necessary to conduct shifting paradigm from a literalist approach merely  focusing on textual and legal meaning to a substantialist approach seeking to capture the moral  ideas and   the original meaning of the syariʻah beyond  the text,  which are trans-historical or transcendental being  and universal (general principle).  This paradigm shifting occurs as  the text is limited while the reality is infinite. Among the substantialist  approaches offered is  the use of maqashid syariʻah and mashlaḥah.  Maqashid syariʻah refers to the essence of God's intention (Law Giver), which is the most essential formulated into five elements, they are: حفظ الدين  (the religion keeping), حفظ النفس  (the soul keeping), حفظ العقل  (the intellect keeping), حفظ النسل (descendant keeping) and المال حفظ (the wealth keeping). Then, hierarchically, maqashid in classical theory is developed into 3 levels: الضرورية  (primary needs /basic  necessity), الحاجية  (secondary needs), and التحسينية  (tertiary needs). Under the argument of maqashid syariʻah,  this Islamic economic concept must be developed, therefore  on the one hand the Islamic economy will not lose its divine morality, but on the other hand it can also develop dynamically, progressively and even ready to handle the  contemporary economic problems. Based on the explanation above, this research is focused on what is the basic philosophy that is the basis of the formulation and development of Islamic economics? This research data is library. The data collection method uses the documentation method, namely: collecting, then reviewing the data collected. After the data is collected, the data is analyzed by reducing data, presenting data in narrative form, and drawing conclusions. This study concludes that the Islamic Economy is closely related to the maqashid syariʻah namely ḥifẓ al-mal. Maqashid syariʻah is the basis for the development of the Islamic economy because it aims at the goal of creating human welfare and happiness by balancing the circulation of property fairly and balanced both personally and socially. Understanding of maqashid syariʻah is a necessity in berijtihad to answer various economic problems. Understanding of maqashid syariʻah is not only needed to formulate macroeconomic policies, but also policies that are microeconomic. In the economic context, maqashid syariʻah has a dual role, namely: as a means of control as well as a social engineering tool to realize human equality. He provides a rational philosophical basis of economic activity. Without the maqashid syariʻah, the understanding and practice of Islamic economics will be narrow, rigid, static, and slow. Islamic economics will lose the spirit and substance of its shari'a. But on the contrary, with the maqashid syariʻah the Islamic economy develops elastic, dynamic, in accordance with the character of the Shariʻah Islam which is universal and relevant for all space and time